Architecture as an Interdisciplinary Field: Towards New Models of Architectural Practice - Ereš, Davor; Mitrović, Jelena (Arhitektura i urbanizam, 2026)
Drawing on Ranko Radović’s position of the inseparability of architectural thought and its materialisation, this text approaches architectural practice as a complex, process-related, and interdisciplinary field. Through Unraveling: New Spaces, exhibited at the 2025 Venice Architecture Biennale, and in relation to the curatorial framework of Carlo Ratti, architecture is understood an open system of relations rather than a finitive construction. The metaphor of the labyrinth and Ariadne’s thread is established as the epistemological and operational model for the contemporaneity of architectural practice, in which the designing focus shifts from the finality of the solution toward the navigation within complexity. The Unraveling: New Spaces project integrates architecture, design, the materiality of wool, and engineering approaches, generating a kinetic and adaptive form responsive to the energy and climate conditions of an ever-changing world, particularly emphasising the need to shift from mitigation toward adaptation. In this sense, architectural practice becomes a field for shaping evolving relationships between the material, social, and ecological conditions. Through collective and interdisciplinary action, Unraveling: New Spaces proposes new approaches to architectural thought and practice within the context of today’s global challenges, affirming the openness, interdisciplinarity, and the relational character of architectural practice as embedded in the temporality of the present.
Keywords: contemporaneity of architecture; interdisciplinarity; exhibition; Architecture Biennale; Ranko Radović